THE MAIN TRENDS IN DEMAND FOR RUSSIAN AUTOMOTIVE MARKET IN 2016 - L. Alimova (Вестник университета)
The article presents the statistics results of sales cars in 2016, lists the factors to stimulate demand in the automobile market during the crisis period. Summarized the principles of benefit programs from the government and automaker, given their impact on the overall dynamics of sales, pre-defined government program to stimulate new car market. Separately allocated sales trend in the secondary car market and its development prospects in Russia, revealed new features of the behavior of car buyers, dealers to consider in today's market conditions.